Novel Immunotherapies and Combinations: The Future Landscape of Multiple Myeloma Treatment - Sonia Morè; Laura Corvatta; Valentina Maria Manieri; Erika Morsia; Antonella Poloni; Massimo Offidani (MDPI AG, 2023)
In multiple myeloma impressive outcomes have improved with the introduction of new therapeutic approaches, mainly those including naked monoclonal antibodies such as daratumumab and isatuximab. However, moving to earlier lines of therapy with effective anti-myeloma drugs led to an increase in the number of patients who developed multi-refractoriness to them early on. Currently, triple- or multi-refractory MM represents an unmet medical need, and their management remains a complicated challenge. The recent approval of new immunotherapeutic approaches such as conjugated monoclonal antibodies, bispecific antibodies, and CAR T cells could be a turning point for these heavily pretreated patients. Nevertheless, several issues regarding their use are unsolved, such as how to select patients for each strategy or how to sequence these therapies within the MM therapeutic landscape. Here we provide an overview of the most recent data about approved conjugated monoclonal antibody belantamab, mafodotin, bispecific antibody teclistamab, and other promising compounds under development, mainly focusing on the ongoing clinical trials with monoclonal antibody combination approaches in advanced and earlier phases of MM treatment.